Pengaruh Komitmen Organisasi Dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Pada PT. Gas Kima Prima Kencana - Surya Kelana Basri; Muhammad Fahmi Razak (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to see the effect of organizational commitment and organizational culture on employee job satisfaction at PT. Prima Kencana Kima Gas. This study uses qualitative and quantitative data as well as data sources, namely primary data with a sample of 42 people. The collected data were analyzed descriptively, meaning that the data obtained in the field was processed using the SPSS 22 application so as to provide a systematic understanding, then statistical calculations of determination, f-test and t-test were carried out. From the results of the regression calculation, a value of Y = 5,228 + 0.587 X_1 + 0.295 X_2 is obtained. This value is the result of a correlation coefficient (r) of r = 0.514 and a coefficient of determination (r2) of 0.717 (71.7). The result of this calculation is the F table test (20.606> 2.85) and the result is the calculation of the T test where tcount>ttable is (3.683>1.684). These results state that there is a positive and significant relationship between organizational commitment and organizational culture on employee job satisfaction at PT. Prima Kencana Kima Gas.